2018
DOI: 10.1021/acs.nanolett.8b01817
|View full text |Cite
|
Sign up to set email alerts
|

Stable, Ultralow Threshold Amplified Spontaneous Emission from CsPbBr3 Nanoparticles Exhibiting Trion Gain

Abstract: Wet-chemically synthesized cesium lead halide nanoparticles have many attractive properties that make them promising as optical gain media, but generally suffer from poor stability under ambient conditions and an optical gain threshold that is widely believed to be dictated by the need for biexcitons. These conditions make it impractical for such particles to be utilized as gain media given the need to undergo repeated stimulated emission processes at above-threshold pump intensities over long periods of time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 37 publications
6
99
1
Order By: Relevance
“…Pterins have not yet been shown to be useful in this capacity in part due to their poor absorption of light in the visible and NIR. There is also wide interest in individual areas of highly emissive and amplified fluorescence materials (51)(52)(53), as well as sensitizers producing high yields of 1 O 2 (38,54). In our case, inroads…”
Section: Discussionmentioning
confidence: 86%
“…Pterins have not yet been shown to be useful in this capacity in part due to their poor absorption of light in the visible and NIR. There is also wide interest in individual areas of highly emissive and amplified fluorescence materials (51)(52)(53), as well as sensitizers producing high yields of 1 O 2 (38,54). In our case, inroads…”
Section: Discussionmentioning
confidence: 86%
“…The insets are the corresponding PL spectra for pump fluences above and below the ASE threshold F th . Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Carrier Dynamics In Metal Halide Perovskite Lasersmentioning
confidence: 99%
“…Jun Pan et al has reported the ASE threshold of the CsPbBr 3 thin films to be 192 and 12 mJ cm −2 under single‐photon and two‐photon pump laser, respectively . Besides, a series of studies were performed to further reduce the ASE or lasing threshold of the CsPbBr 3 QDs thin films …”
Section: Introductionmentioning
confidence: 99%